Principles of Anticancer Drug Development - Garrett-Mayer, Elizabeth; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
A practical guide to the design, conduction, analysis and reporting of clinical trials with anticancer drugs.
Keywords: Medicine; Oncology; Biomedicine; Cancer Research